(untitled) (Journal of Parents and Teachers, 2023)
To face with the educational challenges of the present, we are asked to be creative. Ignatian pedagogy can be a source of inspiration to provide professional responses to the emerging needs. However, this will not be possible with teachers who are exhausted and who do not find meaning in their daily work.